Penguatan Daya Saing Produk Olahan Kopi melalui Workshop Pengemasan, Pemasaran, dan Branding di Desa Peron - Naufal, Muhammad Agnaf; Wulandari, Suci; Rozan, Ajmal; Rahmawati, Maisya; Putri, Ade Anggun Wana; Haris, Amnan (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
Coffee is one of Indonesia’s key commodities that plays a vital role in the national economy and serves as a livelihood for rural communities. Peron Village in Kendal Regency has strong potential in coffee production, yet its marketing remains limited to selling raw beans with low economic value. This study aims to enhance the competitiveness of coffee products through a workshop on packaging, marketing, and branding, focusing on Peronara Tea (cascara) and Kopieron product. The method applied a participatory approach involving the local community, especially the Sekar group, and invited speakers from the Kendal Office of Trade, Cooperatives, and MSMEs. Evaluation was conducted using pre-test and post-test instruments to measure participants’ understanding, and analyzed with the Wilcoxon Signed Rank Test. The results showed a significant difference between pre-test and post-test scores, confirming improved knowledge and skills in food-safe packaging techniques, digital-based marketing strategies, and brand identity development. Therefore, the workshop effectively strengthened the capacity of Peron villagers to manage value-added coffee products. Overall, the program not only fosters more competitive and sustainable coffee-based products but also reinforces local identity, positioning them as potential economic icons of the village.